The Influence Of Product Quality, Price, And Brand Image On Product Purchase Decisions At Faste Coffee - Jenita, Ranfia Jian; Septiani, Monica (UNIVED Press, 2026)
This study aims to analyze the impact of product quality, price, and brand image on consumer purchase decisions at Faste Coffee, particularly among students in Bandarlampung. The method used in this research is multiple linear regression, with a sample of 200 respondents who are Faste Coffee consumers that made purchases in the last three months. The results indicate that product quality, price, and brand image significantly affect purchase decisions simultaneously. Among these three factors, product quality has the most significant impact on purchase decisions, followed by price and brand image. The regression coefficients show that improvements in product quality, competitive pricing, and a positive brand image increase the likelihood of consumers making repeat purchases. Moreover, the ANOVA test reveals that the regression model is highly significant, with Sig. < 0.001, indicating that these three factors contribute greatly to purchase decisions. This study provides valuable insights for Faste Coffee's management to enhance product quality, offer more competitive pricing, and strengthen their brand image through positive consumer experiences. The findings are expected to assist Faste Coffee in formulating more effective marketing strategies, especially to attract young consumers, particularly students as the primary market segment.